APLIKASI PENJADWALAN PEMAKAIAN LAPANGAN FUTSAL MAYANG SPORT CENTER: Information System, Promotion, Booking, CodeIgniter, Bootstrap, MySQL. - -, Afrizal; -, Antonius (LP2M Universitas Nurdin Hamzah, 2018)
People's awareness of exercise is increasing, this increase affects business opportunities in society. Futsal one of the most popular sports, both young and adults, futsal not only to maintain fitness, but also for socialization and release of stress from daily work. Increased futsal sport has spawned a futsal field leasing business. Promotion of futsal field lease is often found in the form of banners in the community. This manual promotion does not give a significant result to futsal field lease transactions. With the advancement of information and communication technology (ICT) this manual way is permitted to do internet. In this study the researchers designed a futsal field promotion and leasing application at the Futsal Field of the Center-based Sport Center Transmitter. This research utilizes Google Map API and Codeigniter application, Bootstrap and MySql database. The purpose of this research is to facilitate the managers to make promotions and facilitate futsal customers to order and search futsal field online.